Mapping of mutants resistant to p-fluorophenylalanine in diploid Aspergillus nidulans, lethal in haploids - N. L. BABUDRI; P. ANGELELLA; G. MORPURGO (Fungal Genetics Reports, 1991)
In a previous paper (Babudri and Morpurgo 1990 Curr. Genet. 17:519-522) we described a new class of para-fluorophenylalanine (FPA) resistant mutants in Aspergillus nidulans. These mutants were obtained by plating UV irradiated diploid conidia on minimal medium (MM) supplemented with FPA (0.188 mg/ml).